Sociology of Cinema. Icelandic Male Identity in Hilmar Oddsson’s Filmography - Bardales Araujo, Nathalia, 1986- (2016)
This study is a BA project for Film Studies at the School of Humanities at the University of Iceland. The project consists of decoding Hilmar Oddsson’s perspective towards the Icelandic male identity by analysing his most remembered films, which are considered both as realistic and representative for Icelanders. Additionally, it will discuss the history of Icelandic films, their background and Hilmar Oddsson’s adherence to the industry as well as ideologies behind the Icelandic film industry, its relation to the European market and the significance of identity for Icelandic culture and filmmakers. Identity, its representations and the experience of the Icelandic male reflected in Oddsson’s films is the main subject analysed in this paper. In order to analyse Oddsson’s representation of identity different reference materials and sources are used with special reference to Enrique del Acebo Ibáñez’s sociological theories. This allows for a better understanding of the basic concept of identity and cultural theory, which expose the anomie of the subject, and its integration and socialisation processes. The result allows understanding Hilmar Oddsson’s male representations and sociocultural conceptions of the Icelandic male identity. Furthermore, methodical observations are essential to recognise the plot, environment, setting and theme presented in Oddsson’s filmography. Finally, the analysis of films, authorship, Icelandic culture, history and theory are applied systematically to separate fiction from reality and likewise to understand Hilmar Oddsson’s interpretation of the male identity in Icelandic society.